Sanak Value in Women’s Land Inheritance Rights: Case Study on Women Inheritance Land Rights in Karangpakuan, Sumedang, West Java - Kurnia, Patricia Beata (The Indonesian Journal of Socio-Legal Studies, 2023)
Karangpakuan Village is one of the villages in Sumedang, West Java, which territory was broken up into multiple parts by the government, as part of its land was submerged in the framework of the creation of the Jatigede Reservoir. Karangpakuan Village is one of the traditional Sunda Priangan villages, in which traditional customary inheritance norms based on bilateral kinship values are still practiced – despite the Islamic background of the community. These bilateral kinship values influence inheritance practices as these are not based on gender, but divided equally while considering other criteria, such as the number of children in the family and the role someone plays in the family. Using a qualitative-ethnographic research method, this article discusses the relationship between bilateral kinship values and customary inheritance practices in Karangpakuan Village. In addition, this article touches upon the issue of how parents reproduce bilateral kinship norms within a Muslim context.